A pressure and temperature cycling test stand with hot-gas bypass control for evaluation of adhesive joints in HVAC&R applications. (April 2022) - Liu, Haotian; Weibel, Justin A.; Geoghegan, Patrick; Groll, Eckhard A.
Abstract: The formation of joints is critical to the long-term reliability with leak-free operation of heating, ventilation, air conditioning, and refrigeration (HVAC&R) systems. Leakages commonly occur due to fatigue failure developing in joined materials from continuous pressure and temperature cycling with mechanical vibration and refrigerant under pressure inside the system. In particular, rapid pressure and temperature changes happen frequently (e.g., multiple times per day) when the system is switched on and off. Therefore, it is important to have an automatically controlled fast-response pressure and temperature cycling (PTC) test stand available to test the performance of refrigeration joints to evaluate new bonding technologies. An innovative PTC test stand with hot-gas bypass control was designed, built, and demonstrated that eliminated the need for an evaporator and ensures rapid transition between different operating conditions. Tests were performed to demonstrate test stand functionality using R410A as the refrigerant to provide pressure and temperature cycles from 600 to 4500 kPa and 5 to 80 °C. A 50-cycle, 5-hour demonstration test was performed with both adhesively bonded and brazed joints following standardized joint testing guidelines. Both joint types survived the test without leaking, suggesting that the adhesive joints have sufficient thermal fatigue resistance along with the conventional brazed joints. Throughout the demonstration, the test stand accurately controlled the setpoint temperatures and pressures while switching the test section between these conditions. The test stand serves as a new approach for pressure and temperature cyclic fatigue testing of joints in HVAC&R systems.